The Role of Social Support for Psychology of Postpartum Mothers in Tembelang Primary Health Care - Hayu Lestari, Rini; Grah Prihartanti, Niken (Journal of World Future Medicine, Health and Nursing, 2023)
Postpartum depression affects around 10-15% of all new mothers, but can be up to 35% higher in the demographic group. In developing countries, the prevalence ranges from 5-25%. 4 One study found 19.2% of new mothers diagnosed with major or minor depression in the first three months postpartum, 7.1% of whom had major depression. In another study of 214 women, 86 of them had symptoms of depression (40.2%), but only 25 (11.7%) were significantly diagnosed as depressed. The number of postpartum mothers in the Tembelang Regional PKM is 47 starting from January to August 2018. This study is an analytical study using correlation analytic design regarding social support roles for postpartum psychology in the Jombang District Auction Area PKM. Test of bivariate data analysis using spearman rho hhe total sample in this study was 47 samples with a total sampling technique. From the analysis of this study it can be concluded that it shows that the model variable has p value <0.05. This means that the social support role variable has a significant relationship to postpartum psychology. It is expected that the results of this study can be used as input for basic health services in the work area associated with early screening for postpartum maternal disorders through postpartum visits.